Memperkokoh Corporate Culture Melalui Mindset dan Family Value - Gendut Sukarno; Muhamat Nur Mustakim (Universitas Mataram, 2021)
Some of the most successful companies in Indonesia come from Family Companies that can reach 3 generations. The organizational culture in the family company is largely determined by the mindset of the family company actors. Besides, many family companies cannot articulate their core values (Family Values) into values that can be applied to business, which must be exemplified by company Leaders. This study aims to examine the concepts of Mindset, Family Value, and Leadership in Organizational Culture. The object of this study is a family company which is engaged in building materials business. The population in this study was all employees at building material companies in Surabaya, with a sample of 30 building material company owners as respondents. The analysis technique used in this study is Partial Least Square (PLS). Based on the study results, it shows that (1) mindset has a significant effect on the organizational culture of the building material family company. (2) Leadership has a significant effect on the organizational culture of the building material family company. (3) Family values have a significant effect on the organizational culture of the building material family company in Surabaya.